Incremental prognostic value of vasodilator stress cardiovascular magnetic resonance over coronary computed tomography angiography in symptomatic patients. (4th February 2022) - Pezel, T; Hovasse, T; Lefevre, T; Sanguineti, F; Unterseeh, T; Champagne, S; Benamer, H; Neylon, A; Toupin, S; Garot, P; Chevalier, B; Garot, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Current guidelines recommend to perform noninvasive functional imaging in patients with obstructive coronary artery disease (CAD) on coronary computed tomography angiography (CCTA). However, the prognostic value of stress cardiovascular magnetic resonance (CMR) over traditional risk factors and CCTA is not known. PURPOSE: To assess the incremental prognostic value of stress CMR beyond traditional risk factors and CCTA in patients with obstructive CAD on CCTA. METHODS: Between 2008 and 2020, consecutive symptomatic patients without known CAD referred for CCTA were screened. Among those, patients with obstructive CAD (at least 1 ≥50% stenosis on CCTA) and referred for functional stress CMR were included and followed for the occurrence of major adverse cardiovascular events (MACE), defined by cardiovascular death or nonfatal myocardial infarction. Univariable and multivariable Cox regressions were performed to determine the prognostic value of CCTA and CMR findings. RESULTS: Of 2, 210 patients who completed the CMR protocol, 2, 038 patients (46.5% male, mean age 69.8 ± 12.2 years) completed the follow-up (median 6.8 [IQR 5.9-9.2] years); 281 experienced a MACE (13.8%). Stress CMR was well tolerated without severe adverse events. Using Kaplan-Meier analysis, inducible ischemia and late gadolinium enhancement (LGE) were significantly associated with the occurrence of MACE (hazard ratio, HR: 4.51, [95%CI: 3.55-5.74]; and HR: 3.32, [95%CI: 2.55-4.32], respectively; both p < 0.001). In multivariable Cox regression, the presence of inducible ischemia and LGE were independent predictors of a higher incidence of MACE (HR: 3.97, [95%CI: 3.43-5.13]; HR: 2.30, [95%CI: 1.52-3.33]; respectively, both p < 0.001). After adjustment, stress CMR findings showed the best improvement in model discrimination and reclassification above traditional risk factors and CCTA findings (C statistic improvement: 0.08; NRI = 0.421; IDI = 0.047). CONCLUSIONS: In symptomatic patients with obstructive CAD of unknown significance on CCTA, stress CMR has an incremental prognostic value to predict MACE over traditional risk factors and CCTA findings.